The Spreading of Vernacular Architecture at the Riverways of South Sumatra, Indonesia - Maya Fitri Oktarini (Indonesian Journal of Geography, 2019)
The development of past settlements was supported by riverways connecting many regions with ethnic diversities. Inter-ethnic dissemination and contact created new cultural combinations. In the southern part of Sumatra, there are two types of stilt houses: highland architecture and lowland architecture. Both architectures are developed by different ethnic groups spread along different riverways. This study focuses on identifying and analyzing the influence of the riverway in the typology of the vernacular stilt house. The architectural typology data was confirmed by field observations and interviews. The analysis was carried out through the Geographic Information System to correlate the influence of the riverway and the ethnic culture on the distribution of the architecture and its transformations. The results show that the river as a transportation route takes up a more dominant role in the spread of architecture than the boundary of the ethnic culture. The cultural significance shows that the highland architecture in the upstream area has a more original and simpler character than the lowland architecture in the downstream area. The riverway exposes diverse cultures to blend into more complex architecture.